Admissible Almost Type Z-Contractions and Fixed Point Results - Said Melliani; Abdelhamid Moussaoui; L. S. Chadli (International Journal of Mathematics and Mathematical Sciences)
In this paper, we introduce a new concept of α-admissible almost type Z-contraction and prove some fixed point results for this new class of contractions in the context of complete metric spaces. The presented results generalize and unify several existing results in the literature.